2023
DOI: 10.1021/acs.est.3c01601
|View full text |Cite
|
Sign up to set email alerts
|

High-Content Screening Discovers Microplastics Released by Contact Lenses under Sunlight

Yuxuan Liu,
Xin Ling,
Runren Jiang
et al.

Abstract: The widespread use of plastic products leads to the ubiquity of microplastics in daily life, while the release of microplastics from long-used contact lenses has not been reported due to the limitations of conventional detection methods. Here, we established a new and rapid method to capture and count microplastics by using a high-content screening system. This method can simultaneously measure the diameter, area, and shape of each plastic particle, and the reliability and applicability of this method were ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A contaminant of concern harboured by plastics are per- and polyfluoroalkyl substances (PFAS) which have been shown to induce immune, cardiovascular, endocrine, and hepatic dysfunction and increase the risk of developing malignancies 21,22 . Contact lenses have been shown to be a source of microplastic exposure, and a recent study showed that contact lens usage was associated with elevated serum PFAS levels among young adults 14,23 . While tear homeostasis and the blink mechanism help with regulating tear volume, their role in clearing microplastics and contaminants of emerging concern remains unexplored 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contaminant of concern harboured by plastics are per- and polyfluoroalkyl substances (PFAS) which have been shown to induce immune, cardiovascular, endocrine, and hepatic dysfunction and increase the risk of developing malignancies 21,22 . Contact lenses have been shown to be a source of microplastic exposure, and a recent study showed that contact lens usage was associated with elevated serum PFAS levels among young adults 14,23 . While tear homeostasis and the blink mechanism help with regulating tear volume, their role in clearing microplastics and contaminants of emerging concern remains unexplored 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of microplastics in vitreous samples were also associated with higher intraocular pressures and the presence of aqueous humour opacities 6 . Contact lenses have been identified as a source of microplastics, with an estimated release of 90,000 particles on the ocular surface from regular wear of ten hours daily over a year 14 . Given the ubiquitous nature of microplastics in plastic packaging, it is conceivable that microplastics may also be present in commercially available eyedrops.…”
Section: Introductionmentioning
confidence: 99%
“…A surprising potential source is intravenous infusion, which can introduce MNPs released from plastic medical products directly into the blood (Table ), , posing a serious potential threat on the human body. Recent studies have also suggested that MNPs can be accidentally introduced into the human body during surgery and while inserting contact lenses. , However, these potentially important human exposure pathways remain unclear. While it is crucial to focus on the primary pathways through which MNPs enter the human body, including ingestion, inhalation, and dermal exposure, the significance of accidental pathways cannot be overlooked, particularly those that directly introduce MNPs into the bloodstream, such as intravenous infusion.…”
Section: Sources Of Mnps In the Human Bodymentioning
confidence: 99%